2017
DOI: 10.1093/icesjms/fsx073
|View full text |Cite
|
Sign up to set email alerts
|

Towards a broader perspective on ocean acidification research

Abstract: Ocean acidification (OA) continues to be one of the most studied single topics in marine science. Almost 800 articles on OA appeared in 2016 alone. Forty-four of those were published in a special themed issue of the ICES Journal of Marine Science, “Towards a broader perspective on ocean acidification research.” Submissions to that themed initiative continued well beyond the original deadline and were so numerous that we decided to publish this—a second OA-themed issue—which contains an additional 33 articles. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…OA has been the most‐studied topic in marine science in recent times (Browman, 2017). As such, many OA experiments have been conducted, usually exposing organisms to experimental conditions based on scenarios modelled for open ocean waters, typically simulating present and near‐future surface ocean pH levels.…”
Section: Introductionmentioning
confidence: 99%
“…OA has been the most‐studied topic in marine science in recent times (Browman, 2017). As such, many OA experiments have been conducted, usually exposing organisms to experimental conditions based on scenarios modelled for open ocean waters, typically simulating present and near‐future surface ocean pH levels.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of anthropogenic carbon into the atmosphere has caused the oceans to warm and acidify, but the joint effects of these changes remain unclear for the majority of marine species (Caldeira and Wickett 2003; Browman 2017). Changes in pH and temperature are not uniform across the marine environment.…”
mentioning
confidence: 99%
“…Ocean acidification has been shown to reduce swimming performance in some fish species but responses to ocean acidification are often complex (Munday 2014;Browman 2017;Clark et al 2020). In fact, studies have reported an increase, a decrease, or no significant change in aerobic scope associated with swimming at high pCO 2 (Munday et al 2009;Couturier et al 2013;Rummer et al 2013;Esbaugh et al 2016).…”
Section: Climate Change and Locomotor Performance In Teleost Fishesmentioning
confidence: 99%
“…As a consequence, some individuals may be able to acclimate over a relatively long period of time while some populations may rapidly adapt to the changes in their environment across generations favoring physiotypes that are resilient in the new conditions (Munday 2014;Ryu et al 2018). Organisms can also employ other solutions, such as shifting their geographic range, to respond to environmental challenges (Harvey et al 2013;Rosa et al 2014;Browman 2017). Changes in locomotor performance, behavior and geographic range at large and small scale may have cascading and unexpected effects on biotic interactions, community structures and ecosystem functioning (Harvey et al 2013;Di Santo et al 2020).…”
Section: Introductionmentioning
confidence: 99%